Soft-Tissue Reconstruction Using Biologic Tissue Matrix: Where Do We Stand? - Ferdinand Köckerling (Frontiers Research Topics, 2018)
Soft-tissue reconstruction for a variety of surgical conditions, such as abdominal wall hernia, hiatal hernia, stomal hernia, anal fistula and pelvic floor replacement remains a challenge. There is an insufficient level of high-quality evidence in the literature on the value of bioprosthetics for soft-tissue reconstruction. An expanded knowledge about their clinical efficacy is urgently needed.